Implementasi Media Permainan Edukatif Ular Tangga Untuk Meningkatkan Motivasi Peserta Didik Dalam Pembelajaran Pendidikan Jasmani Ditinjau Dari Prinsip Pengajaran Dan Asesmen di SDN Kampungdalem 4: Penelitian - Tito Raka Nanda Amirunni’am; Ruruh Andayani Bekti; Ali Masrofi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the implementation of the educational board game "Snakes and Ladders" in enhancing students' learning motivation in Physical Education at SDN Kampungdalem 4, viewed from the principles of teaching and assessment. The research employs a PTK approach using observation, interviews, and documentation techniques. The findings indicate that the Snakes and Ladders game creates a more enjoyable learning environment, increases student engagement, and strengthens conceptual understanding through experiential learning. From a teaching perspective, this educational game supports active and collaborative learning, while from an assessment standpoint, it helps teachers evaluate students' comprehension in a more natural and less burdensome way. Thus, the Snakes and Ladders educational game can be considered an innovative strategy to enhance student motivation and improve the effectiveness of Physical Education learning in elementary schools.